PENILAIAN ORGANISASI PERANGKAT DAERAH (OPD) TENTANG OTORITAS VETERINER DALAM KEBIJAKAN PENANGGULANGAN RABIES DI PROVINSI BANTEN - Joko Ismadi; Bambang Sumiarto; Widagdo Sri Nugroho; Erwan Agus Purwanto (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2020)
AbstractLegislation No 41 Year 2014 about Amendment of Legislation No 18 Year 2009 about Livestock and Animal Health explains that Veterinary Authority is a government institution, formed in order to deal with decision making of anything related to animal health, by involving veterinarians and mobilizing all related professional lines, to identify problems, deciding policies, coordinating policy implementation, and handling the field operations.This research material uses the result from a group of respondents, which represents 36 Regional organizations (OPD), they are: 9 OPD Technical services, supervising animal health (keswan) and veterinary public health (kesmavet), 9 OPD Health services, 9 OPD Regional development planning services, and 9 OPD Regional staffing services (BKD), for regencies, and cities in Banten Province. Data collection is done using two methods, quantitatively by using data from all 36 OPD, and qualitatively by using observation, interviews, dan questionnaires.First 5 questions: 1). Are the organization bureaucratic? 2). Positions, roles, and authority of veterinarians? 3). Is the veterinary authority regarding rabies control at agencies, clinics, and animal health center already in line with the implementation? 4). Strategic policy and 5). Integrated, directed, and continuous program regarding public awareness of rabies, for rabies control in provincial or regency government. The answers are as follows, Technical services of animal health (keswan) and veterinary public health (kesmavet) : 0%, 33,33%, 77,78%, 100% and 77,78% answered yes; 100%, 66,67%, 22,22%, 0% and 22,22% answered no. Health services: 22,22%, 66,67%, 88,89%, 44,44% and 44,44% answered yes; 77,78%, 33,33%, 11,11%, 55,56% and 55,56% answered no. Regional development planning services (Bappeda), 33,33%, 88,89%, 66,67%, 11,11% and 11,11% answered yes; 66,67%, 11,11%, 33,33%, 88,89% and 88,89% answered no; Regional staffing services (BKD) 88,89%, 77,78%, 55,56%, 0% and 0% answered yes; 11,11%, 22,22%, 44,44%, 100% and 100% answered no. Next questions: 6). Cooperations between OPD, 7). Regional Policy 8). Veterinarian openings and 9). Enforcement and improvement of otovet institutions. The answers are as follows: Technical services of keswan kesmavet: 33,33%, 44,44%, 77,78% and 100% answers yes; 66,67%, 55,56%, 22,22% and 0% answers no. Health services: 55,56%, 22,22%, 0% and 77,78% answers yes; 44,44%, 77,78%, 100% and 22,22% answers no. Regional development planning services (Bappeda), 33,33%, 33,33%, 33,33 and 100% answers yes; 66,67%, 66,67%, 66,67% and 0% answers no; while Regional staffing services (BKD) 11,11%, 11,11%, 100% and 66,67% answers yes, 88,89%, 88,89%, 0%, !00% and 33,33% answers no.In conclusion, after scoring the questionnaire, the results for OPDs supervising animal health (keswan) and veterinary public health (kesmavet) otovet are as follows: Technical services with 9 OPDs, 4 OPDs scores well and 5 OPDs scores poor. Health services with 9 OPDs, 4 OPDs scores well and 5 OPDs scores poor. Regional development planning services (Bappeda) with 9 OPDs, 4 OPDs scores well and 5 OPDs scores poor. Regional staffing services (BKD) with 9 OPDs, 1 OPD scores well and 8 OPDs scores poor.Keywords: Veterinary authority; Regional organizations (OPD), control rabies, rabies